A green, versatile, and facile strategy for anti-biofouling surface with ultra-high graft density polyethylene glycol - Wenjie Liu; Suqin He; Hao Liu; Zeyu Shou; Kaiyuan Huo; Hongping Xiang; Aihan Feng; Wei Lu; Na Li (Journal of Nanobiotechnology)
Abstract Implantable catheters are susceptible to severe complications due to non-specific protein adhesion on their surfaces. Polyethylene glycol (PEG) coatings, the gold standard for resistance to non-specific protein adhesion, present a challenge in achieving high-density grafting, which significantly restricts their use as anti-biofouling coatings. Herein, we exploited the strong interaction between polyphenols (PCs) and polycations (K6-PEG) to graft PEG onto the surface of PC-Cu (A network of metal polyphenols composed of proanthocyanidins and metal copper ions, with expectation for the coating with excellent resistance to non-specific protein adhesion (PC-Cu@K6-PEG). The introduction of K6-PEG resulted in enhanced stability and modulus of PC-Cu, as well as a reduction in the surface adhesion energy and contact angle of PC-Cu. In contrast to previously reported PEG coatings, PC-Cu@K6-PEG exhibited a markedly elevated grafting density of PEG (4.06 chains/nm²), which was more than double the highest value previously reported (1.9 chains/nm²), due to the diffusing ability of K6-PEG throughout the PC-Cu networks. PC-Cu@K6-PEG displays robust resistance to a variety of proteins, microbials, and platelet attachment, thereby preventing thrombosis. The coating ability of PC-Cu onto diverse substrates, combined with the simple, straightforward and environmentally benign process of fabricating PC-Cu@K6-PEG, suggests that this strategy has significant potential for use in anti-biofouling surfaces.